Effects of cationic head groups of ionic liquid on micellization in aqueous solution of PEO-PPO-PEO triblock copolymer. Issue 11 (2nd November 2017) - Vekariya, Rohit L.
ABSTRACT: The interaction of ionic liquids (ILs) with non-ionic triblock copolymer, Pluronic® P123 in aqueous solutions has been investigated using DLS, surface tension, and viscosity measurements. The addition of ILs increased the Critical Micelle Concentration (CMC) of P123, which appears to be logistic. As the added IL enhances the solubility of PPO moiety (and PEO), which makes them to behave like a more hydrophilic block copolymer that would be micellized at high copolymer concentration. The DLS data is in good agreement to the results observed from surface tension measurements. Viscosity results show the propensity in micellar size reduction upon addition of ILs, and hence, intrinsic viscosity decreases as compared to pure P123 aqueous solution. The results are studied and discussed as a function of cationic head groups of N -octyl-pyridinium/imidazolium chloride based ILs. GRAPHICAL ABSTRACT: